Trinity, revelation, and reading: a theological introduction to the Bible and its interpretation - Swain, Scott R. ca. 20./21. Jh. (Criminal Practice Ser., 2011)
Trinity, Revelation, and Reading (TRR) is a theological introduction to the Bible and biblical interpretation. The overarching thesis is that neither the Bible nor biblical hermeneutics can be understood or practiced properly apart from an appreciation of their relationship to the triune God and his gracious economy of redemption. Scott Swain treats the role of the Word in the saving economy of the triune God, the role and status of Scripture as the Word of God, the nature of biblical reading as a covenantal enterprise, as well as a host of other related topics. These topics are addressed by w